Pengaruh Belanja Pemerintah Terhadap Pertumbuhan Ekonomi: Studi Kasus Provinsi Kalimantan Utara Tahun 2013 – 2023 - Patadungan, Rante Datu; Isnanto, Khotib Umam; Fitrianingtyas, Adeva; A, Aslan (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
North Kalimantan’s economic growth is reflected in the decline in poverty rates. In the third quarter of 2023, North Kalimantan’s economic growth showed economic development indicators that were directly proportional to the social welfare of the community. This can be seen from the positive graph of economic growth and the decline in the open poverty rate (TPT) in the same period. Government spending is focused on improving and protecting the quality of life of the community, which is an obligation for the region, through improving the health, education, public and social facilities, basic services, and developing social security sectors as regulated in Law Number 32 of 2004. This study aims to analyze the effect of regional spending on economic growth in North Kalimantan Province in the 2013–2023 period. Based on the results of the analysis using the Classical Assumption Test (including Linearity Test, Normality Test, Autocorrelation Test, Multicollinearity Test, and Heteroscedasticity Test), Hypothesis Test, F Test, T Test, and R-Square Test, it was found that, first, simultaneously, government spending has a significant effect on economic growth in North Kalimantan Province. Second, several types of government spending show significant effects on economic growth in different directions. In particular, government spending on public service and economic functions has a significant positive effect on economic growth, indicating the importance of investment in infrastructure and economic development to increase overall economic activity. On the other hand, government spending on health functions shows a significant negative effect on economic growth in North Kalimantan Province.